2015
DOI: 10.2174/1389201015666141202101909
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization and Analgesic Effect of Inclusion Complexes of Essential Oil from Hyptis pectinata L. Poit Leaves with β-Cyclodextrin

Abstract: The formation of inclusion complexes of Hyptis pectinata essential oil (EOHP), with potent activities such as anti-nociceptive, anti-inflammatory, among others, with β -cyclodextrin (β-CD), was obtained by slurry (SC) and paste procedures (PC). The gas chromatography coupled to the mass spectrometry (GC/MS) analysis demonstrated a total of 36.4% monoterpenes and 63.6% sesquiterpenes in the EOHP. The major components of EOHP were identified as (E)- caryophyllene (54.07%). The analysis of samples (PM, PC and SC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 23 publications
3
19
0
1
Order By: Relevance
“…The major compounds reported in this study corroborate other works involving the essential oil of H. pectinata, in which the main chemical compounds commonly detected were: pcymene (33.7%), β-pinene (6.95%), β-caryophyllene (7.00-54.07%), caryophyllene oxide (1.98-38.05%), calamusenone (1.85-48.00%), , 2008, ARRIGONI-BLANK et al, 2010, RAYMUNDO et al, 2011, MENEZES et al, 2015.…”
Section: Resultssupporting
confidence: 90%
“…The major compounds reported in this study corroborate other works involving the essential oil of H. pectinata, in which the main chemical compounds commonly detected were: pcymene (33.7%), β-pinene (6.95%), β-caryophyllene (7.00-54.07%), caryophyllene oxide (1.98-38.05%), calamusenone (1.85-48.00%), , 2008, ARRIGONI-BLANK et al, 2010, RAYMUNDO et al, 2011, MENEZES et al, 2015.…”
Section: Resultssupporting
confidence: 90%
“…The poor bioavailability of hydrophobic drugs demands the use of high doses to overcome subtherapeutic levels in plasma. 7 To solve this limitation, a large number of studies have been published describing new delivery systems such as inclusion complexes with cyclodextrins [8][9][10][11] and nanoparticles. 7,[12][13][14][15] Nanoparticle systems have been considered promising carriers of therapeutic drugs, and the application of these particles as carriers of natural compounds has been extensively studied over the past few years.…”
mentioning
confidence: 99%
“…For instance, the complexation of Hyptis pectinata L. EO with β-CD improved its analgesic effect in a mice model [34]. Also Bomfim et al observed that β-CD complexation increased in vivo tumor growth inhibition capacity of Annona vepretorum EO [32].…”
Section: Interaction Between Phytochemicals and Cyclodextrinsmentioning
confidence: 99%